Analysis of the Wenchuan aftershock data - Siew, Hai-Yen; Pooi, Ah Hin * (2012)
We analyse the aftershocks of theWenchuan earthquake in 2008 using a multivariate non-normal distribution fitted to the observations for the variables selected from the inter-aftershock times, depths, magnitudes, sines and cosines of the azimuths, slant angles, and slip angles of a number l + 1 of consecutive aftershocks. From the multivariate distribution, we find a prediction interval for the occurrence time of the next aftershock when the values of the other selected variables are given. The performance of the prediction interval is assessed by its ability to cover the observed occurrence time of the next aftershock, and by the average length of the interval. A similar prediction interval is also obtained for the magnitude of the next aftershock. It is found that as l increases from 1–4, while the performance of the prediction interval for the magnitude of the aftershock improves only slightly, that of the prediction interval for the inter-aftershock time improves quite substantially. TheWenchuan model with l = 4 is also used for predicting the inter-aftershock time in the 2011 Tohoku earthquake. It is found that the drop in the coverage probability of the prediction interval for the next aftershock time in the Tohoku earthquake is only about 8%, indicating that the characteristics of the aftershocks at different locations of the earth might have some similarities